The Cytotoxic Effect of the Extract of Anchusa strigosa (Him Him) Grown in Jordan Against Different Cancer Cell Lines - Arwa Omar Al-Khatib; Iqbal Khateeb; Rana Dahab; Naseer Al-Rawi (مجلة بغداد للعلوم)
Anchusa strigosa - prickly alkanet from Boraginaceae grows in roadsides, and fields of a broad range of habitats from mediterranean woodlands, to steppe vegetation, to true desert. It is commonly known as" him him" or "lisan al thawr". Anchusa can withstand hard weather conditions and hence is widely cultivated. The color of its flowers can range from pure white to deep cobalt blue. Various parts of A. strigosa are used in traditional medicine for treating several diseases or symptoms, such as abdominal pain, bronchitis, cough, and diarrhea. The goal of this study was to examine the cytotoxic effect of the crude extract of A. strigosa roots and leaves and their fractions against various tumor cell lines: adenocarcinoma MCF-7, human breast ductal carcinoma T-47D; human breast carcinoma MDA-MB-231; and colorectal carcinomas Caco-2. In conclusion the antiproliferative effect was assessed by SRB assay where it showed that the phytochemical constituents in the leaf part of the plant (A. strigosa) do have more potential in depressing the proliferation rate of the cell lines than the root part.